Regulating electric double layer in non-fluorinated ether electrolyte enables high-voltage and low-temperature lithium metal batteries - Renfei Zhao; Yuanhang Gao; Zuosu Qin; Yuelin Li; Tao Zhang; Anqiang Pan; Ning Zhang; Renzhi Ma; Xiaohe Liu; Gen Chen (Advanced Powder Materials)
The poor oxidation stability of ether-based solvents has long been a major challenge limiting their practical application. To enhance the oxidative stability of ether-based electrolytes, the physicochemical properties of various glycol dimethyl ethers are screened, and diglyme (G2) is selected as the sole solvent for the electrolyte. Lithium bis(fluorosulfonyl)imide (LiFSI), a highly dissociative salt, is used as the primary salt; while lithium nitrate (LiNO3) and lithium difluorophosphate (LiDFP), which have small ionic sizes and strong binding energies, are added as secondary salts. The resulting electrolyte can modulate the electric double layer structure by NO3− and DFP− on the cathode side, leading to an increased Li+ concentration that is originally repelled by the cathode. Additionally, the oxidation stability of the electrolyte is improved and the formed electrode-electrolyte interphase is more uniform and stable, thereby enhancing the electrochemical performance of the cells. As a result, cells assembled with a total of 1 M ternary lithium salts in G2 solvent can operate at high voltage of 4.4 ​V. The Li||NCM811 ​cells maintain 80.2% capacity retention after 270 cycles at room temperature, with an average Coulombic efficiency of 99.5%, and exhibit 88.4% capacity retention after 200 cycles at −30 ​°C.